Dietary Choline Protects Against Cognitive Decline After Surgery in Mice - Maurer, Sara V.; Kong, Cuicui; Terrando, Niccolò; Williams, Christina L. (Frontiers in Cellular Neuroscience, 2021)
Perioperative neurocognitive disorder (PND) is a common complication following procedures such as orthopedic surgery. Using a mouse model of tibial fracture and repair surgery, we have previously shown an increase in neuroinflammation and hippocampal-dependent cognitive deficits. These changes were ameliorated with the addition of a cholinergic agonist. Here, we sought to examine the effects of a high-choline diet for three weeks prior to tibial fracture surgery. We evaluated memory using novel object recognition (NOR) as well as young neurons and glial cell morphology at 1 day and 2 weeks post-surgery. At both time points, tibial fracture impaired NOR performance, and dietary choline rescued these impairments. Astrocytic density and hilar granule cells increased 1 day after tibial fracture, and these increases were partially blunted by dietary choline. An increase in young neurons in the subgranular zone of the dentate gyrus was found 2 weeks after tibial fracture. This increase was partially blunted by choline supplementation. This suggests that shortly after tibial fracture, hippocampal reorganization is a possible mechanism for acute impaired memory. These findings together suggest that non-pharmaceutical approaches, such as pre-surgical dietary intervention with choline, may be able to prevent PND.